2015
DOI: 10.1002/adfm.201502636
|View full text |Cite
|
Sign up to set email alerts
|

Large Multipurpose Exceptionally Conductive Polymer Sponges Obtained by Efficient Wet‐Chemical Metallization

Abstract: 6182 wileyonlinelibrary.com fi brous segments. Sponges are typically highly porous and easily permeable by gases. Metallization of such sponges could give novel polymer/metal composites with highly interesting properties for a variety of applications, e.g., electrodes in fuel cells, membranes, fi ltration, thermal insulation, heating, ultralight constructions, and catalysis. Well-established metallization techniques for polymer materials include physical or chemical vapor deposition and galvanization. [ 4 ] Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 33 publications
1
40
0
3
Order By: Relevance
“…By using the hot chromic acid-sulfuric acid cleaning of plastic surface followed by activation with tin chloride and palladium chloride solutions, the conventional plating processes for metallization of polymer are commonly expensive and toxic [20,21]. Therefore, many latest studies [22][23][24][25] have been reported to develop low-cost and environmentally friendly methods for improvement of adhesion between metal coating and the substrate.…”
Section: Introductionmentioning
confidence: 98%
“…By using the hot chromic acid-sulfuric acid cleaning of plastic surface followed by activation with tin chloride and palladium chloride solutions, the conventional plating processes for metallization of polymer are commonly expensive and toxic [20,21]. Therefore, many latest studies [22][23][24][25] have been reported to develop low-cost and environmentally friendly methods for improvement of adhesion between metal coating and the substrate.…”
Section: Introductionmentioning
confidence: 98%
“…Ultralight carbonaceous aerogels are attractive for their fascinating features in terms of low apparent density, good electrical conductivity, large surface area, high porosity, and chemical inertness, which have been widely studied for electrical, biomedical, environmental, and energy applications . In the ultralow range below 5 mg cm −3 , relatively few aerogels currently exist: fullerene aerogels (>1.5 mg cm −3 ), graphene sponges (>0.3 mg cm −3 ), aerographite (>0.22 mg cm −3 ), carbon nanotube aerogels (>0.16 mg cm −3 ), and carbon nanoribbon foams (>4.3 mg cm −3 ) .…”
mentioning
confidence: 99%
“…The droplets of water, diiodomethane, toluene, and n ‐hexadecane could easily roll off from the surface of the 13° tilted SAME sponge owing to the existence of the air cushion between the sponge and the droplets. [9a] The SAME sponge therefore can float on the surface of toluene. Once immersed in toluene by an external force, the SAME sponge was reflective in toluene (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Guo and co‐workers reviewed the recent progress about the applications of superhydrophobic 3D‐PMs for oil/water separation . Greiner and co‐workers reported preparation of conductive and superhydrophobic 3D‐PMs by efficient wet‐chemical metallization, which could be highly interesting for heating and insulation devices …”
Section: Introductionmentioning
confidence: 99%